CI CoE and CI4Resilience's Creating a Thriving Workplace Workshop Report - Brock, Joel; Christopherson, Laura; Deelman, Ewa; Ferreira da Silva, Rafael; Kee, Kerk; Murillo, Angela; Nabrzyski, Jarek; Romsos, Chris; Rynge, Mats; Vahi, Karan; Whitcup, Wendy (Zenodo, 2021)
As a result of talking with NSF Major Facilities (MFs) staff at the 2019 NSF Workshop on Connecting Large Facilities and Cyberinfrastructure (CI) and interviews conducted with MF managers in the spring of 2020, the CI CoE Pilot concluded that MFs have specific needs and experience unique challenges with staff recruitment, retention, and development that are not currently met. As a result, in June 2021, the CI CoE Pilot and CI4Resilience (which explores the impact of the pandemic on MF CI personnel) brought together staff from MFs in a one day, virtual workshop to discuss their experiences and the challenges they face with developing and sustaining a vibrant workforce. This workshop focused on three main MF workforce challenges: working in remote or distributed teams, working in non-traditional environments, and creating a work culture that taps into intrinsic motivations. The workshop discussed the creative ways MFs are meeting these challenges while making work with an MF attractive to potential hires and worthy of existing staff’s continued engagement. For instance, two MF workshop speakers spoke of innovative training opportunities they have designed to strengthen staff development. One is a simulated computing training environment in the States aimed at preparing IceCube staff to work efficiently during their long stays at the South Pole, away from friends and family and the usual day-to-day routines. Those that participate in this training feel more confident and are more successful overall when working at the South Pole. The other is an RCRV program that allows early-career oceanographers to serve on training cruises. This provides them with the opportunity to learn how to best collaborate and communicate with ship operators (the ship’s CI professionals). The alumni of this program have reported additional successes in their work as a result of the program. MFs offer some unique experiences to their staff, providing them with the ability to be a part of something larger than themselves— performing work that has lasting impact on science, society, and the world we live in. Tech companies may not be able to boast opportunities to participate in Nobel Prize winning work. The workshop discussed ways for MFs to leverage their assets, such as providing opportunities for impactful work, to attract new talent and strengthen the fidelity of existing staff. Finding: MFs present unique challenges in the area of workforce development, often requiring a complex set of inter-disciplinary skills and personal attributes. Recommendations: 1) The lessons learned and successes reported at the workshop should be shared with the rest of the MF community. 2) The enthusiastic participation in and response to the workshop has confirmed that future efforts to continue this discussion and tackle these MF-specific challenges is necessary to continue to advance science, engineering, and the cyberinfrastructure that makes the science possible.